The Use of the Prism Adaptation Test and Monocular Occlusion in the Preoperative Preparation of a Patient with Strabismus - Zarębska-Lindner, Magdalena; Rosa, Agnieszka (Okulistyka (Warszawa), 2022)
In patients with strabismus the prism adaptation test and monocular occlusion allow revealing the maximum angle of deviation before strabismus surgery. Furthermore, these procedures are helpful in differentiating the types of strabismus.